Refinement of farm specific technologies in cluster of villages of Balaghat district (Chhattisgarh Plain) - Bisen, N K; Bisen, U; Shrivastava, A K; Bisen, S; Rai, S K; Sarvade, S S; Thakur, R K; Bisen, Dharna; Jaiswal, Aparna; Gowswami, Pooja (Indian Farming, 2022)
.